Essential fatty acids in farmed tambaqui (Colossoma macropomum) from the Brazilian Amazon Area - Tatiana Soares dos Santos; Ernané dos Santos Souza; Neura Bragagnolo; Antonio Rosendo da Costa; José Jordão Filho; Neiva Maria de Almeida (Acta Scientiarum. Animal Sciences, 2022)
The goal of this study was to determine the essential fatty acids of the total lipids of the fillet, head and orbital cavity tissue from farmed tambaqui (Colossoma macropomum) fish from a Brazilian Amazon area. The tambaqui were acquired from different fish farms in the Roraima state, located at Western Brazilian Amazon. The meat, the head and the fatty tissue from orbital cavity were dissected for lipid extraction and analysis of fatty acids by gas chromatography. The fatty acids were quantified in mg g-1 of total lipids using C23:0 as an internal standard. The nutritional quality of the lipids was determined by using the atherogenicity and thrombogenicity indices, and also by the ratio between hypocholesterolemic / hypercholesterolemic fatty acids. The orbital cavity tissue had the higher concentration amount of linoleic and α-linolenic acid, whereas the fillet had higher docosahexaenoic acid (DHA). The eicosapentaenoic acid (EPA) concentration was: 1.28, 0.97, 1.71 mg g-1 of total lipids, in the filet, in head, and in orbital cavity tissue, respectively. All essential fatty acids were detected in the three parts analyzed. The nutritional quality of the total lipids from the head and from the orbital cavity tissue was similar to the fillet.